2018
DOI: 10.5539/ijef.v10n2p35
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between RMB Exchange Rate and Chinese Trade Balance: Evidence from a Bootstrap Rolling Window Approach

Abstract: This study inspects the fundamental relationship between the exchange rate and the trade balance in China. The outcome shows that the real effective exchange rate and trade balance in China has no causal relationship. Though, seeing structural changes in two series, we got the result those both long-run and short-run associations using full-sample data are wobbly, which proposes that the full-sample causation tests can"t be relied upon. Then, using time-varying rolling window method to reexamine the dynamic fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Nawaz and Ghani (2018) established a negative relationship between devaluation and output growth for Pakistan, and Onakoya, Johnson, and Ajibola (2019) also found a negative relationship between devaluation and trade balance for Nigeria in the long run. Masih, Liu, and Pervaiz (2018) found no relationship between devaluation and trade balance for China. The indirect effect of devaluation is also seen empirically such as Olawole, Adebayo, and Idowu (2018) found negative impact of financial openness on economic growth for Nigeria, while Ali (2016) found a positive relationship between currency evaluation and interest rate for Pakistan.…”
Section: Literature Reviewmentioning
confidence: 90%
“…Nawaz and Ghani (2018) established a negative relationship between devaluation and output growth for Pakistan, and Onakoya, Johnson, and Ajibola (2019) also found a negative relationship between devaluation and trade balance for Nigeria in the long run. Masih, Liu, and Pervaiz (2018) found no relationship between devaluation and trade balance for China. The indirect effect of devaluation is also seen empirically such as Olawole, Adebayo, and Idowu (2018) found negative impact of financial openness on economic growth for Nigeria, while Ali (2016) found a positive relationship between currency evaluation and interest rate for Pakistan.…”
Section: Literature Reviewmentioning
confidence: 90%
“…The elasticity approach relates the effect of exchange rate changes on TB to the price elasticities of demand and supply for exports and imports. Studying this relationship conditional to the sum of the price elasticities of demand for exports and imports is called Marshall-Lerner Condition (Baek, Koo, and Mulik, 2009;Bahmani-Oskooee et al, 2016;Drama, 2010;Masih, Liu and Pervaiz, 2018;Tutuianu, 2015). This approach studies this relationship as a net effect of real exchange rates changes on both prices and volume of traded goods 5 (Ali et al, 2014;Andersson and Styf, 2010;Chiloane et al, 2014;Choi, 2017;Hussain and Bashir, 2012;Lencho, 2013).…”
Section: The Elasticity Approachmentioning
confidence: 99%
“…The J-curve phenomenon started as a dynamic representation of Marshall-Lerner Condition. It studied how the effects of devaluation on TB can vary over time as elasticities changes (Andersson and Styf, 2010;Chiloane et al, 2014;Drama, 2010;Masih et al, 2018;Musawa, 2014). In the short-term, demand for exports and imports are less-elastic.…”
Section: The Elasticity Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, the nexus between the exchange rate and EG is an extensively debated issue in the literature and is the central macroeconomic goal of economic policy agenda across the globe (Easterly & Levine, 1997;Fischer, 1992;Knight, Loayza, & Villanueva, 1993;Most & De Berg, 1996). Many other studies investigating the impact of exchange rate uncertainty on EG reported mixed findings (Ahmad, Hayat, Luqman, & Ullah, 2012;Akhtar & Malik, 2000;Ali & Anwar, 2016;Baron, 1976;Bini-Smaghi, 1991;Cushman, 1983;De Grauwe & Verfaille, 1988;Gros, 1987;Hasan & Khan, 1994;Hassan, Fausat, & Baba, 2016;Kandil, 2008;Kappler, Reisen, Schularick, & Turkisch, 2013;Khan, 1995;Kohler, Manalo, & Perera, 2014;Masih, Liu, & Pervaiz, 2018;Nawaz & Ghani, 2018;Yang, 1997). Numerous studies in recent years have provided compelling evidence regarding the effect of exchange rate uncertainty on the EG of developing economies (Algaeed & Algethami, 2022), Saudi Arabia (Khan, 2021), Bangladesh (An, Binh, & Cam, 2020), and ASEAN (Matthew et al, 2021).…”
Section: Introductionmentioning
confidence: 99%